Fishing devices of the river Siang in Arunachal Pradesh, India - Biplab Kumar Das; Ngasepam Romen Singh; Prasanna Boruah; Devashish Kar (Journal of Fisheries, 2015)
Fish is one of the best sources of animal protein of the food. Fishing and hunting are the oldest profession of all mankind since man began his search of food. Traditional fishing catching devices which were operated in River Siang, Arunachal Pradesh have been studied with respect to its operation, structure and productivity. The small depicted work highlight 13 different types fish catching devices, which have been classified into 5 different types viz., (i) Encircling Gear (Khewali Jal, Angtha Jal and Ber Jal or Jeng Jal) (ii) Entangling Gear (Langi or Current Jal and Phansi Jal) (iii) Scooping Gear (Sip Jal and Thela Jal) (iv) Hooks and Line fishing (Nal Barshi and Doogabanshi) (v) Traps (Chepa, Dingora, Polo, and Kholaha). The present study was carried out from June 2012 to July 2013 in a 58km stretch of River Siang in East Siang district of Arunachal Pradesh. Some methods can be considered as traditional as well as non-traditional since they are well known in some other states of North-East as well as also in the country with some different kind of variation. Various fishing techniques depend on various behavioral pattern and microhabitat type of fishes.